Strategies to control virus and virus-like diseases: state of the art and perspectives for stone fruits - Dunez J. (Stone fruit viruses and certification in the Mediterranean countries: problems and prospects, 1998)
The application of sanitary selection procedures has contributed to a considerable improvement of the quality of fruit crops, mainly in the case of pathogens that are not naturally spread. In the Mediterranean region, two diseases cannot be easily controlled by the sanitary selection i.e. sharka, transmitted by aphids, and the apricot chlorotic leaf froll whose vector is still obscure. Breeding programmes for resistance to these two pathogens have been set up. The low number of natural resistance sources has led to approaches like interspecific hybridization. Remarkable results have been obtained through transgenosis: some plum and apricot lines resistant to sharka have been obtained. Transgenic plants, jointly with conventional plant breeding methods, may contribute to limit the impact of sharka on fruit production.